A PROTOCOL FOR SHOOT REGENERATION FROM LEAVES PETIOLES TISSUE CULTURE OF NEEM TREES ( Melia azedarach ) - Mozahim K. AL- Mallah (Mesopotamia Journal of Agriculture)
Shoots were regenerated from petioles – derived callus on solidified Murashige and Skoog (MS) medium supplemented with 1.5 mg / l BA only and MS medium containing 4.0 mg / l IBA and 1.0 mg / l BA . The percentage of shoot formation was 30.0 % . The regeneration frequency was reasonable to obtained sufficient shoots by this method . This simple protocol is the first report in tissue culture of this woody plant which encourage other researchers to worke other studies in tissue culture of neem . Moreover , callus culture will be useful to obtain a wide range of industrial plant products .